Do age and sex influence on functional movement in school-age children? (¿Influyen la edad y el sexo en la funcionalidad del movimiento de niños en edad escolar?) - Garcia-Pinillos, Felipe; Párraga-Montilla, Juan; Roche-Seruendo, Luis E; Delgado-Floody, Pedro; Martínez-Salazar, Cristian P; Latorre-Román, Pedro A (Retos, 2019)
Abstract. The aim of this study was to determine the influence of age and sex on the functional movement in Spanish primary school children. A group of 172, 6–11 years old children (83 girls and 89 boys), participated in this study. The main outcome measures were the Functional Movement ScreenTM (FMS), sex and chronological age of children. The ANCOVA (BMI as a covariate) revealed significant differences between age groups (p=0.003) but no between-sex differences (p≥0.05) in FMS total score. As for individual FMS tests, significant differences between age groups (p